Evaluation Service Quality in Processed Food Importation Certification: A Combination of SERVPERF and Importance-Performance Analysis - Fatati Fatati; Liane Okdinawati (AIBPM Publisher, 2021)
This research aims to evaluate and increase service quality to acquire customer satisfaction from the Directorate. Due to the close correlation to customer satisfaction, service quality has been considered a critical factor for service providers' success. Therefore, consumers' perception becomes a crucial component in assessing service quality. The public service quality evaluation was based on the guideline elements from the Minister of Administrative and Bureaucratic Reforms regulation No.14 of 2017. The SERVPERF was applied to measure service quality according to the customers' perception of responsiveness, assurance, tangibles, empathy, and reliability. At the same time, Importance-Performance Analysis (IPA) was used to identify indicators in need of improvement. The result reveals the lowest mean performance score of the empathy dimension, and the five dimensions have a positive correlation to overall service quality. Assurance, empathy, and tangible were significant predictors. Furthermore, based on the results of the IPA, sub-variables Q5, Q29, Q31 are importantly perceived by the customers but the low performance of the Directorate.